Aproximações conceituais sobre linguagem na área de educação física - Barros, Allan Delmiro (2017)
The present study is part of the research line Pedagogical Practice and Professional Training in Physical Education of the area of concentration of Culture, Education and Human Movement of the Associated Program of Physical Education UPE / UFPB, linked to the ETHNÓS Group – Study Group Ethnographic studies in Physical Education and Sports. Based on the recognition that physical education is located, according to the National Curriculum Parameters – PCNs (BRASIL, 2000), in the scope of Languages, Codes and their Technologies, we discuss how the conceptual approximations about language were constituted in the field of physical education. It presents as general objective: to analyze the conceptual approaches on language in the area of physical education. And, in its specificity, it seeks: to approximate the reflections on language and the appropriation that physical education has configured in the historical course through the science of language and the philosophy of language; To identify the concept of language from the scientific productions of the area of physical education; To identify the conceptual correlations between language in/with physical education in PCNs High School – Languages, Code and its Technologies/Physical Education and in PCN+ High School. Of a qualitative nature, the research technique used is indirect documentation, through a bibliographical research that will allow the researcher to reach a broad knowledge of what one intends to study, since it will increase the possibility of compiling data about his study. In order to do so, we conjecture three paths that will give the proper alignment for the composition of the methodology of this research, in which: in the first course, are the reflections on the Science of language and the philosophy of language, which constitute our theoretical contribution; In the second course, the theoretical mapping was made that allowed the identification of the appropriation of the concept of language in the scientific productions of the physical education area, in the articles published in periodicals as well as in the dissertations and theses of the area in Brazil; And, in the third course, the preliminary analytical reading of national curricular documents (PCNs) and (PCN+) is configured. After analyzing the chapter dealing with science and philosophy of language and aligning with the mapped productions of the area of physical education, it was possible to infer empirical categories that denote language not only as communication, present in the literature of the area, but which language It is also action, emotion, symbolic meanings, power, culture, history, which penetrates and is imbued in the Being of the social Being that influences and is influenced by the characteristic compilations of language.